Incorporating fairness motives into the impulse balance equilibrium and quantal response equilibrium concepts: An application to 2x2 games - Alessandro Tavoni (Fondazione Eni Enrico Mattei (FEEM), 2009)
Substantial evidence has accumulated in recent empirical works on the limited ability of the Nash equilibrium to rationalize observed behavior in many classes of games played by experimental subjects. This realization has led to several attempts aimed at finding tractable equilibrium concepts which perform better empirically; one such example is the impulse balance equilibrium (Selten, Chmura, 2008), which introduces a psychological reference point to which players compare the available payoff allocations. This paper is concerned with advancing two new, empirically sound, concepts: equity-driven impulse balance equilibrium (EIBE) and equity-driven quantal response equilibrium (EQRE): both introduce a distributive reference point to the corresponding established stationary concepts known as impulse balance equilibrium (IBE) and quantal response equilibrium (QRE). The explanatory power of the considered models leads to the following ranking, starting with the most successful in terms of fit to the experimental data: EQRE, IBE, EIBE, QRE and Nash equilibrium.
Keywords: C72; C91; D01; D63; 330; Fairness; Inequity aversion; Aspiration level; Impulse balance; Quantal Response; Behavioral economics; Experimental economics